Akurasi dan Evaluasi Terjemahan Arab-Indonesia dalam Takarir Film “From the Ashes” (2024) - Nurhayati, Peti; Maulani, Abdullah; Suparno, Darsita; Abdullah, Abdullah (Deskripsi Bahasa, 2025)
This research aimed at analyzing the translation quality and cultural adaptation aspects in a translated movie of "From the Ashes" (2024). Starring Alshaima Tayeb, Khayria Abu Laban, and Adwa Fahad, this movie depicted how Saudi Arabian women navigated social-cultural dimensions while dealing with surrounding conflicts. This movie was chosen due to its idiomatic expressions in Arabic dialogue, which were translated into Indonesian subtitles for Netflix. Employing a descriptive qualitative method and translation evaluation approach, this research revealed several translation inaccuracies related to the adaptation from Arabic to Indonesian. In terms of accuracy, the researcher found the inaccuracies in conveying the intended messages to the target language, resulting in a misunderstanding. Regarding acceptability, the researcher discovered a lack of naturalness in the transfer of the source text into the target language. This is evident in the use of inappropriate diction. Furthermore, the use of ineffective sentences hinders comprehension.